Living Related Donor Kidney Transplantation in Libya: A Single Center Experience - Elusta Ahmed; Shawish Taib; Mishra Anuj; Ajaj Husni; Milud Nagib; Shebani Abdulhafidh; Abdulmola Tamer; Altajori Osama; Ethuish Ehtuish (Saudi Journal of Kidney Diseases and Transplantation, 2008)
The aim of this study is to report the experience from a single center in Libya, on the prevailing live-related kidney transplantation program. The results of three years work on kidney transplantation at the Tripoli Central Hospital (National Organ Transplant Program) in Libya were evaluated. The transplant program was launched on 17 th August, 2004 and 135 patients have been transplanted since then till 17 th August, 2007. All donors and recipients were screened thoroughly prior to transplant and monitored closely in the post-transplant period. Our immuno-suppressive protocol was cyclosporine-based. Among the 135 accepted pairs, donors and reci-pients were genetically-related in 133 cases (98.5%) and emotionally-related in two others. The mean donor age was 37 ± 9.5 years (range 18-56 years) and recipient age 37 ± 13.6 years (range 7-67 years). There were 95 males (70.4%) and 40 females (29.6%) among the recipients while among the donors, there were 102 males (75.6%) and 33 females (24.4%). Delayed graft function was seen in three patients (2.2%), acute rejection in six (4.4%), post-transplant urinary tract infection in six (4.4%), pneumonia in three (2.2%), ureteric kink in two (1.5%) and urine leak in four (3.0%). Graft survival at 36 months was 93.3% while patient survival at the same period was 96.3%. This report indicates that the results of our transplant program are good and comparable with other international programs.